2013
DOI: 10.1007/s10508-013-0099-8
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Protective Factors Among Trans Adults

Abstract: A recent study indicated a suicide attempt rate of 41 % among trans (e.g., trans, transgender, transexual/transsexual, genderqueer, two-spirit) individuals. Although this rate is alarming, there is a dearth of literature regarding suicide prevention for trans individuals. A vital step in developing suicide prevention models is the identification of protective factors. It was hypothesized that social support from friends, social support from family, optimism, reasons for living, and suicide resilience, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
113
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 49 publications
10
113
2
4
Order By: Relevance
“…The unique effect of depression on ideation is unsurprising given past literature on the topic (see Hoffman, 2014 for a review), however, the results of the significant interaction indicate that social support from a significant other, and not from family or friends, buffers the negative impact of harassment and rejection on suicidal ideation. The current findings are interesting given that most studies have largely focused on or identified the significant impact of perceived general, family, or peer support on quality of life (Baser et al, 2016), mental health (Bariola et al, 2015; Bockting et al, 2013; Nemoto et al, 2011; Pflum et al, 2015), and suicide (Moody & Smith, 2013). While the current findings are generally in line with prior work identifying social support helping to mitigate the detrimental impact of minority stress on suicidality in trans people (Moody & Smith, 2013), in addition to the broader literature on social support and suicide (Kleiman & Liu, 2013), the presence of significant effects by social support from a significant other suggests future work would benefit from this inclusion.…”
Section: Discussionmentioning
confidence: 94%
“…The unique effect of depression on ideation is unsurprising given past literature on the topic (see Hoffman, 2014 for a review), however, the results of the significant interaction indicate that social support from a significant other, and not from family or friends, buffers the negative impact of harassment and rejection on suicidal ideation. The current findings are interesting given that most studies have largely focused on or identified the significant impact of perceived general, family, or peer support on quality of life (Baser et al, 2016), mental health (Bariola et al, 2015; Bockting et al, 2013; Nemoto et al, 2011; Pflum et al, 2015), and suicide (Moody & Smith, 2013). While the current findings are generally in line with prior work identifying social support helping to mitigate the detrimental impact of minority stress on suicidality in trans people (Moody & Smith, 2013), in addition to the broader literature on social support and suicide (Kleiman & Liu, 2013), the presence of significant effects by social support from a significant other suggests future work would benefit from this inclusion.…”
Section: Discussionmentioning
confidence: 94%
“…Trans people are subjected to invisibility in institutional settings [22], high levels of discrimination and rejection [21, 23], harassment and violence [2426], and poverty [7, 27]. Trans-related social exclusion has been associated with increased lifetime and past-year suicide attempts [2, 6, 28], while social and family support appear to be protective [2, 29]. Determinants of suicide risk in the broader population, including depression, substance misuse, and poverty [9, 10] are also elevated among trans persons [6, 30, 31], but are consistently attributed to social exclusion and victimization [23, 25, 28, 32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests an inverse relationship between fear of death and suicidal attempt so that people who are afraid of death are less likely to report suicidal ideation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, friends can have a role in changing the adolescents' attitudes and prevent their suicidal attempts (19,31). Negative attitudes towards suicide attempts in the society and a person's consideration of what will be said about him/her after suicide attempt can prevent him/her from doing so (37,38).…”
Section: Discussionmentioning
confidence: 99%